Psssst! It's me---the Bogeyman - Park, Barbara, 1947-; Kroninger Stephen (New York : Atheneum Books for Young Readers, 1998)
A genuine, creepy-crawly, blood-chilling, spine-tingling Bogeyman, who lives under beds, reveals something he soon regrets.
"An Anne Schwartz book."